PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 002 PULAU RAMBAI KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Erma Yenni; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to increase the student’s IPS outcomes at fifth grade in SDN 002 Pulau Rambai by using direct learning model. Problems that exist in SDN 002 Pulau Rambai are (1) the average student’s learning outcomes is low, (2) students noisier when studying IPS, (3) students are less active when learning, (4) most students are often out or permission upon learning. The subject are fifth grade student’s SDN 002 Pulau Rambai that totally is 24 who is 10 male students and 14 female students. Object in the research is to increase the student’s IPS outcomes by using direct learning model at fifth grade in SDN 002 Pulau Rambai. This research is two cycles, the each cycle consisting of two meetings and test. The average percentage of the students before using the model is 45.8%, is increased 66.7% in the first cycle and increase 83.3% in the second cycle. The average student’s learning outcomes increase from base score to first cycle is 9.5% , the second cycle average student’s learning outcomes is 20.7%. Basically the student’s learning outcomes can be show of direct learning model can to increase the student’s IPS outcomes at fifth grade in SDN 002 Pulau Rambai subdistrict Kampar Timur Kampar Regency.Keywords: Direct Learning Model, IPS learning outcomes